Utilization of Rhizosphere Antagonistic Microorganisms to Suppress The Damping Off Disease Caused by Sclerotium rolfsii Sacc. on Soybean - Ika Agustin Rusdiana; Antok Wahyu Sektiono; Ika Rochdjatun Sastrahidayat (Journal of Tropical Plant Protection, 2022)
Damping off on soybean is caused by Sclerotium rolfsii Sacc. It is a disease that can reduce production of soybean because and even lead to crop failure. The aims of this research are to obtain antagonist microorganisms in the rhizosphere of soybean to suppress damping off disease and determine the mechanism and than the effect of antagonist isolates on the incidence damping off disease of in vivo. The results of in vitro research obtained 13 isolates. However, only 5 isolates showed antagonism activity consisting of 4 bacterial isolates with antibiosis mechanism and 1 fungal isolate with mycoparasite mechanism against S. rolfsii. The results of in vivo research indicated that antagonist isolates could suppress damping off disease. The highest percentage of damping off disease incidence was observed in the control (80.71%) and the lowest percentage of the Trichoderma sp. (24.76%).